2017
DOI: 10.1097/phh.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Seeking Health Care: Comparison of Veterans and the General Population

Abstract: Study results suggest a possible link between VA access problems and veterans' behavior in seeking needed healthcare, which may be creating disparities in the effectiveness of care for this vulnerable and deserving population. Our study provides evidence of self-reported care delay among veterans. More studies are necessary to further understand factors in relation to delaying seeking care among veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Using the Medical Expenditure Panel Survey from 2006 to 2011, Bernard and Selden (2016) find that nonelderly Veterans were comparable to and non-Veterans in terms of health care access after controlling for various characteristics (Bernard and Selden 2016). However, using data from the 2010-2011 Health Tracking Household Survey, Lee and Begley (2016) find that, after controlling for various characteristics, Veterans were more likely than those with private insurance to report delayed needed medical care (Lee and Begley 2016). On a national level, this study shows that the majority of Veterans across the United States do not live in Shortage Area Counties, a finding consistent with Bernard and Selden (2016).…”
Section: Discussionmentioning
confidence: 97%
“…Using the Medical Expenditure Panel Survey from 2006 to 2011, Bernard and Selden (2016) find that nonelderly Veterans were comparable to and non-Veterans in terms of health care access after controlling for various characteristics (Bernard and Selden 2016). However, using data from the 2010-2011 Health Tracking Household Survey, Lee and Begley (2016) find that, after controlling for various characteristics, Veterans were more likely than those with private insurance to report delayed needed medical care (Lee and Begley 2016). On a national level, this study shows that the majority of Veterans across the United States do not live in Shortage Area Counties, a finding consistent with Bernard and Selden (2016).…”
Section: Discussionmentioning
confidence: 97%
“…It is obvious that access to health services will improve patient satisfaction. In a study, in this field, it was suggested that there is a possible link between veteran affair access problems and veterans' behavior in seeking the needed health care, which may be creating disparities in the effectiveness of care for this vulnerable and deserving population (Lee and Begley, 2017;Rad, Kavosi and Arefnezhad, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Further, veterans may experience greater delays in accessing healthcare than non-veterans as eye care is the third most-utilized service in the VA and growing rapidly. [27][28][29] The combination of high risk for eye disease and challenges in accessing eye care makes how eye care is provided to veterans an important consideration.…”
Section: Methodsmentioning
confidence: 99%